EVALUATION OF THE EFFECTIVENESS OF SRIKANDI APPLICATION IMPLEMENTATION IN ARCHIVE MANAGEMENT AT THE JAMBI PROVINCE PUPR OFFICE USING THE DELONE AND MCLEAN MODEL APPROACH - Tumanggor, Tambatua; Dedy Setiawan; Yolla Noverina (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
The success of the SRIKANDI application in archive management within the Department of Public Works and Spatial Planning (PUPR) of Jambi province is examined in this study using the DeLone and McLean Information System Success Model. Effective archive management is necessary to support organizational effectiveness, particularly in government organizations that handle substantial amounts of documents and records. Using digital technologies like SRIKANDI is expected to increase the efficacy, accuracy, and accountability of archive management as technology advances. The six key components of the DeLone and McLean model (system quality, information quality, service quality, utilization, user satisfaction, and net benefits) were chosen because they provide a detailed framework for evaluating the efficacy of information systems. Employees of the Jambi Province PUPR Office who have used the SRIKANDI application were given questionnaires to complete in order to gather data for this study, which takes a quantitative approach utilizing a survey method. The study's findings should give a comprehensive picture of how the SRIKANDI program helps with better archive management and point out areas that need improvement. In order to enable more contemporary, effective, and efficient archive governance, the Jambi Province PUPR Office will use the results as strategic input to enhance the quality of information services and optimize the use of the SRIKANDI application.